The Extracellular Protein, Transthyretin Is an Oxidative Stress Biomarker - Sharma, Meesha; Khan, Sheeza; Rahman, Safikur; Singh, Laishram Rajendrakumar (Frontiers in Physiology, 2019)
The extracellular protein, transthyretin is responsible for the transport of thyroxin and retinol binding protein complex to the various parts of the body. In addition to this transport function, transthyretin has also been involved in cardiovascular malfunctions, polyneuropathy, psychological disorders, obesity and diabetes, etc. Recent developments have evidenced that transthyretin has been associated with many other biological functions that are directly or indirectly associated with the oxidative stress, the common hallmark for many human diseases. In this review, we have attempted to address that transthyretin is associated with oxidative stress and could be an important biomarker. Potential future perspectives have also been discussed.